(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the use of anthroponyms in Ubaydulla Solikh oglu Zavqi’s works. The anthroponymic units: names, nicknames, nicknames are classified and the poet’s skill as a nominator is revealed. Names are divided into lexical-semantic groups and their meaning is explained. The etymological analysis of some names serves to express how the onomastics of the Uzbek language is reflected in Zavki’s work.